Quercetin supplementation in metabolic syndrome: nutrigenetic interactions with the Zbtb16 gene variant in rodent models - Kábelová, Adéla; Malínská, Hana; Marková, Irena; Hüttl, Martina; Liška, František; Chylíková, Blanka; Šeda, Ondřej (Genes & nutrition, 2024)
BACKGROUND: Quercetin is a promising phytochemical in treating abnormalities associated with metabolic syndrome (MetS). This study aimed to explore the morphometric, metabolic, transcriptomic, and nutrigenetic responses to quercetin supplementation using two genetically distinct MetS models that only differ in the variant of the MetS-related Zbtb16 gene (Zinc Finger And BTB Domain Containing 16). RESULTS: Quercetin supplementation led to a significant reduction in the relative weight of retroperitoneal adipose tissue in both investigated strains. A decrease in visceral (epididymal) fat mass, accompanied by an increase in brown fat mass after quercetin treatment, was observed exclusively in the SHR strain. While the levels of serum triglycerides decreased within both strains, the free fatty acids levels decreased in SHR-Zbtb16-Q rats only. The total serum cholesterol levels were not affected by quercetin in either of the two tested strains. While there were no significant changes in brown adipose tissue transcriptome, quercetin supplementation led to a pronounced gene expression shift in white retroperitoneal adipose tissue, particularly in SHR-Zbtb16-Q. CONCLUSION: Quercetin administration ameliorates certain MetS-related features; however, the efficacy of the treatment exhibits subtle variations depending on the specific variant of the Zbtb16 gene.